The Influence of Leadership Style, Work Morale, and Work Discipline on Work Productivity at MSMEs Mendali Mas Bandar Kidul Kota Kediri - Cahyono, Ridho Noer Cahyono (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze the effect of leadership style, work enthusiasm and work discipline on employee productivity at UMKM Mendali Mas Bandar Kidul Kediri. Design/Method/Approach: This study uses a quantitative approach with a causal associative design to examine the causal relationship between the research variables. Data were collected from 32 employees using a structured questionnaire based on a 5-point Likert scale. Data were analyzed using multiple linear regression, t-test, F-test, coefficient of determination and correlation test using SPSS version 27 software. Research Findings: The results showed that leadership style, morale, and work discipline have a significant effect on work productivity, both partially and simultaneously. Morale was found to be the most dominant variable affecting work productivity. Theoretical contribution/Originality : This study makes a theoretical contribution by expanding the knowledge on the relationship between leadership style, morale, and work discipline in the context of MSMEs in Indonesia. This study also adds to the literature on internal factors that influence labor productivity, which have been less explored in previous studies. Practitionel/Policy implication: The findings of this study provide recommendations for MSMEs to adopt participative leadership styles, develop employee motivation programs, and implement consistent discipline policies to sustainably improve work productivity. Research Limitations: This study is limited to one MSME in a particular region with a small sample size, so the findings cannot be generalized to other MSMEs in Indonesia. This study also focuses only on three internal variables without considering external factors that may be influential. Keywords: Leadership Style, Work Morale, Work Discipline, Work Productivity, MSMEs.